Thoughts of intern and resident doctors living in İstanbul about mobbing at work - CÖBEK ÜNALAN, GÜLRU PEMRA (My University, 2020)
Background: Mobbing is considered as acts of psychological and physical attacks such as all kinds of ill-treatment, threats, humiliation by one or more employee against another employee which is carried out systematically and consistently in the purpose of intimidating individuals in the workplace. People working particularly in health services are working under more risk than other service areas and professions. Research questions: What is the thoughts of residents and interns living in Istanbul about mobbing? Have they exposed any mobbing act and showed any reaction? Method: A qualitative design applied to 38 participants with face to face interviews by the help of a semi-structured form. Participants are chosen with a purposeful sampling method from three different types of institutions. Interviews were conducted and lasted at least 20 minutes. Transcripts are created after the interviews are audio recorded. Analysis is performed by researchers working independently. The researchers reached a consensus on the list of codes that are common in their list. The entire list of codes has been revised until all researchers agreed. Results: Main-themes in our research;1-Mobbing perception. 2-Reactions against mobbing acts 3-Seniority and authority 4-Mobbing and environment 5-Attitude of person who does mobbing(temperament, manner) 6-Prevention of mobbing. Many of the participants said that mobbing was something coming from superiors, learned from them and applied in time and because of that it should be interrupted from the top seniority in order to prevent mobbing. Participants emphasized on some expressions for the feelings caused by mobbing such as "emotionally depressed", "feeling inadequate", "exhausted", "feeling meaningless", "despair", "unhappiness", "hating from work environment", "discouraging". Conclusions: Mobbing is a serious problem in the hospital setting. Determining the boundaries of tasks/jobs, increasing the effectiveness of the law, investigating the complaints, not approving mobbing acts as possible but talking about it and fight against mobbing are leading proposals to cope with mobbing.
Keywords: Mobbing; intimidation; medicine; intern; resident; asistant; seniority; healthcare sector